Expression of the transcription factor, PP ARs in immune cells of balb/c mice - Letchumanan, Mobana (2004)
Peroxisome proliferator activated receptors (PP ARs) are ligand-activated transcription factors that belong to the nuclear hormone receptor superfamily. Despite significant involvement in the lipid metabolism, little is known about the expression pattern and the role of different PP ARs in immune regulation. Emerging evidence suggests that PP ARs may act as negative immunomodulators. To provide further insight into the role ofPPARs in the immune system, the expression patterns of PPARa., PPARyl and PPARy2 in peritoneal macrophages and splenocyte-derived T lymphocyte subsets, CD4+ and CD8+ cells of balb/c mice were studied. Total RNA from each of the cell subsets was extracted, reverse-transcribed to eDNA and the expression of PPARa, PPARyl and PPARy2 quantified by Real-Time PCR using specific primers and probes. The expression levels were then calculated per J..lg total RNA and statistically analyzed using statistical software. In addition, cytokine expression profiles in the selected immune cells were also assessed using multiplex PCR method. The results obtained in the present study demonstrate that all the immune cell subtypes predominantly express PP ARyl suggesting the probable involvement of this transcription factor in immune response or other biological functions of these cells. The study also further confirms that lymphocytes express PP ARa. CD8+ lymphocytes showed the lowest expression of all PP AR isoforms compared to other immune cells suggesting minimal involvement of the PP ARs in the immune response mediated by these cells. In addition baseline expression levels of various cytokines in immune cell subsets in young adult mice also were showed in the current study.